Management of stage 1 renal cell cancer in patients immunosuppressed for organ transplantation or autoimmune disease - Ghasemzadeh, Ali; Wendt, Eric T.; Dolan, Brendan; Craig, Juliana; Allen, Glenn O.; Abel, E. Jason; Shapiro, Daniel D. (Frontiers in Urology, 2023)
Objective To describe the treatment and outcomes of patients who are medically immunosuppressed due to prior organ transplantation or autoimmune disease with clinical T1 renal cell carcinoma (cT1). Methods An institutional database of patients treated for RCC was queried for patients with cT1 RCC and on chronic medical immunosuppression at the time of RCC diagnosis. The outcomes for patients undergoing (1) surgery, (2) ablation, or 3) active surveillance (AS) are described. Results Between 2010 and 2022, 74 medically immunosuppressed patients with RCC were identified and treated using surgery (n = 29), ablation (n = 33), or AS (n = 12). Seven (58%) AS patients underwent deferred treatment (six ablations and one nephrectomy) due to tumor growth. For surgery patients and ablation patients, the 30-day readmission rates [17% and 9%, respectively (p = 0.7)], and 90-day complication rates [24% and 21%, respectively (p = 0.9)] were similar. One (3%) surgical patient and two (6%) ablation patients recurred locally. Despite being immunosuppressed, only one (3%) surgical patient, one (3%) ablation patient, and no AS patients progressed to metastatic disease. No significant differences were noted for the local recurrence-free rates, metastasis-free rates, and overall survival for the three cohorts (p > 0.05 for all). Conclusions Patients with stage one RCC with medical immunosuppression can be safely managed through surgery, thermal ablation, or active surveillance, with similar outcomes to historical series of non-immunosuppressed patients. Future prospective studies should investigate shared decision making in this patient cohort and include discussion of less aggressive options that minimize morbidity but preserve oncologic control.